3. Mics & Sounds - Bjork C (Pod Uni podcast, 2021)
Producer-host Dr Collin Bjork introduces you to 3 types of microphones you might use (shotgun, cardioid, and omnidirectional) and 3 types of nonhuman sounds you might gather in the field (room tones, ambient sounds, and characteristic sound effects).